Characteristic map of working mediums in closed loop two-phase thermosyphon: Thermal resistance and pressure. (25th June 2020) - Bai, Ye; Wang, Liang; Zhang, Shuang; Lin, Xipeng; Peng, Long; Chen, Haisheng
Highlights: Performance of closed loop two-phase thermosyphon with 9 popular fluids. Chart illustrating the optimum operating temperature range for 9 popular fluids. Criterion of fluid selection for closed loop two-phase thermosyphon. Abstract: As an effective heat transfer unit, closed loop two-phase thermosyphon is widely applied due to simple structure and natural circulation. The type of fluid filled in the loop determines the heat transfer performance. To study the effect of fluid type on the closed loop two-phase thermosyphon, nine fluids are analyzed numerically, namely R-116, CO2, R-125, R-134a, R-1234ze, R-600a, R-600, R-123 and ethanol. The color maps of thermal resistance and pressure are drawn relative to changes in evaporator temperature and condenser temperature. The figure illustrating the optimum operating temperature range of those working fluids is obtained. It is concluded that the larger the critical temperature of the fluid is, the larger the optimum operating temperature is. Then the criterion of fluid selection in terms of thermal resistance is achieved with dimensionless calculation of evaporator temperature and condenser temperature.